Increased sulfur tolerance of Pt/KL catalysts prepared by vapor-phase impregnation and containing a Tm promoter - Jacobs, Gary (2000)
Pt/KL catalysts are highly active and selective for the aromatization of hexane, but they display a very high sensitivity to even small concentrations of sulfur in the feed. Tm-containing Pt/KL catalysts were prepared by incipient wetness impregnation (IWI), ion exchange (IE), and vapor-phase impregnation (VPI) methods. The platinum morphology resulting from the addition of thulium and platinum sequentially, using the VPI method, yielded the greatest enhancement to the aromatization performance of the Pt/KL catalysts. The presence of thulium in the sequential VPI Pt/Tm/KL catalyst resulted in a catalyst with higher platinum dispersion than that in an unpromoted VPI catalyst. VPI catalysts provided more finely dispersed Pt clusters than either than either conventional IWI or IE methods. From temperature programmed oxidation of poisoned catalysts, thulium acted as a getter for sulfur, thus, delaying the poisoning of platinum under sulfur-containing feeds. The initial activity of the Tm-promoted VPI catalysts was higher than that of the unpromoted Pt/KL VPI catalysts, suggesting that thulium may directly modify platinum or even participate in accelerating the aromatization reaction.